2019
DOI: 10.3390/cancers11020251
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analyses Reveal Genomic Features of FOXM1 Overexpression in Cancer

Abstract: FOXM1 is frequently overexpressed in cancer, but this has not been studied in a comprehensive manner. We utilized genotype-tissue expression (GTEx) normal and The Cancer Genome Atlas (TCGA) tumor data to define FOXM1 expression, including its isoforms, and to determine the genetic alterations that promote FOXM1 expression in cancer. Additionally, we used human fallopian tube epithelial (FTE) cells to dissect the role of Retinoblastoma (Rb)-E2F and Cyclin E1 in FOXM1 regulation, and a novel human embryonic kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
162
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(176 citation statements)
references
References 71 publications
14
162
0
Order By: Relevance
“…BDPs are often enriched with specific histone modifications H3K4me3, H3K9ac, H3K27ac, and H3K4me2 (Bornelov et al, 2015) and, in agreement, ENCODE data revealed that H3K4me3 and H3K27Ac are enriched in bimodal peaks at the F/R-BDP, suggesting correlated transcriptional activity in both directions ( Figure S3). ENCODE data also revealed an E2F1 peak, consistent with E2F's known involvement in BDP regulation and prior data identifying E2F1 as a regulator of FOXM1 expression ( Figure S3) (Barger et al, 2019;Barger et al, 2015;Chen et al, 2014;Millour et al, 2011).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…BDPs are often enriched with specific histone modifications H3K4me3, H3K9ac, H3K27ac, and H3K4me2 (Bornelov et al, 2015) and, in agreement, ENCODE data revealed that H3K4me3 and H3K27Ac are enriched in bimodal peaks at the F/R-BDP, suggesting correlated transcriptional activity in both directions ( Figure S3). ENCODE data also revealed an E2F1 peak, consistent with E2F's known involvement in BDP regulation and prior data identifying E2F1 as a regulator of FOXM1 expression ( Figure S3) (Barger et al, 2019;Barger et al, 2015;Chen et al, 2014;Millour et al, 2011).…”
Section: Resultssupporting
confidence: 82%
“…The FOXM1/RHNO1 BDP (F/R-BDP) region contains a CpG island (CGI), a common feature of BDPs ( Figure S3) (Antequera, 2003;Takai and Jones, 2004;Wakano et al, 2012).BDPs are often enriched with specific histone modifications H3K4me3, H3K9ac, H3K27ac, and H3K4me2 (Bornelov et al, 2015) and, in agreement, ENCODE data revealed that H3K4me3 and H3K27Ac are enriched in bimodal peaks at the F/R-BDP, suggesting correlated transcriptional activity in both directions ( Figure S3). ENCODE data also revealed an E2F1 peak, consistent with E2F's known involvement in BDP regulation and prior data identifying E2F1 as a regulator of FOXM1 expression ( Figure S3) (Barger et al, 2019;Barger et al, 2015;Chen et al, 2014;Millour et al, 2011).The data presented above suggested that FOXM1 and RHNO1 are co-regulated. In agreement, we observed highly significant correlation of FOXM1 and RHNO1 expression in normal and cancer tissues, and in both mouse and human samples ( Figure 1B).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The iBRD4 plasmids were constructed using the pCW57-GFP-2A-MCS backbone (Addgene, 71783), which was a gift from Adam Karpf and previously described 83 .…”
Section: Plasmid Constructionmentioning
confidence: 99%